2021
DOI: 10.1080/1550428x.2021.1902448
|View full text |Cite
|
Sign up to set email alerts
|

“I Was Just Fed up of Not Being Myself”: Coming out Experiences of White British Divorced and Separated Gay Fathers

Abstract: Before the so-called "gayby boom" in the 1990s the most common pathway to parenthood for gay men was heterosexual marriage. Since the 1990s most research on gay parenting has focused on intentional gay fathersthose parenting after coming out as gayand the experiences of post-heterosexual divorce gay fathers (PHGF) have largely been overlooked, even though they remain the largest group of gay fathers. Furthermore, most research on this group, and on gay fathers more broadly, has been conducted in the US, with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
(177 reference statements)
0
5
0
Order By: Relevance
“…These behavioral protective factors included compartmentalizing, serosorting, and volunteering. Many researchers have discussed in the past decade the protective, albeit likely transient, effects that compartmentalizing has afforded to gbMSM who chose to categorically keep their sexual identities, encounters, activities, and HIV statuses separate from their religious identities, families, and work lives [32,[35][36][37][38][39][40]. In these discussions, compartmentalizing was not considered as a behavioral protective factor that could potentially foster the resilience of gbMSM to HIV/AIDS, and more so, as a factor that could be valued and utilized in the development of interventions that are dedicated to fostering HIV resilience.…”
Section: Considering and Valuing Behavioral Protective Factors In The Development Of Interventions That Foster Resilience To Hiv/aidsmentioning
confidence: 99%
“…These behavioral protective factors included compartmentalizing, serosorting, and volunteering. Many researchers have discussed in the past decade the protective, albeit likely transient, effects that compartmentalizing has afforded to gbMSM who chose to categorically keep their sexual identities, encounters, activities, and HIV statuses separate from their religious identities, families, and work lives [32,[35][36][37][38][39][40]. In these discussions, compartmentalizing was not considered as a behavioral protective factor that could potentially foster the resilience of gbMSM to HIV/AIDS, and more so, as a factor that could be valued and utilized in the development of interventions that are dedicated to fostering HIV resilience.…”
Section: Considering and Valuing Behavioral Protective Factors In The Development Of Interventions That Foster Resilience To Hiv/aidsmentioning
confidence: 99%
“…Compartmentalization has been a behavioral strategy that many (including racial and ethnic minority) MSMLWH have come to rely on over the years to gain a degree of protection from the negative impacts of barriers to promoting HIV resilience such as racism and HIV stigma [68][69][70][71]. Although compartmentalization may not directly promote HIV resilience among racial and ethnic minority MSM, its protective effects prevent the decline of their resilience and provides them a reprieve from the sometimes unrelenting harmful effects of systemic factors such as racism and HIV stigma on their wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is some evidence that gay fathers may experience particular difficulties negotiating the transition to fatherhood, especially in the context of heteronormativity [46]. For instance, research has shown how some men struggle to negotiate the identity "gay father", particularly when faced with heterosexist norms and feelings of internalised shame [47]. Third, the route to gay fatherhood via surrogacy presents unique logistical, legal, and emotional challenges [10,39].…”
Section: Psychological Distress In Gay Fathersmentioning
confidence: 99%